(3QMdI GdYHOQis - (3QRjf Hf eYGhjI Hf YeGQ GdYHOQj GdCfOdSjs
(3ChdgG (B:s
(3GdMeO ddg MeO eYJQa HGdJYUjQ hHYO aEffi bGUO HYO GSJNGQI Gddg SHMGfg Edi JbjjO eG Cecf JbjjOI hQSe eG JjSQ QSMI ai NHQ GdQMdI Zdi HdGO GdeaJQb s
(3BNQgG (B:s
(3bGd jG YHO GdUeO djcf Chd GUdGMI jHjf UdGM faSg aEf Yjhfge eabhOI HYjfgG aGdMSf YfOge eG aYdJ hGdbHM YfOge eG JQcJ s
(3fSNJ HQSe NRGfI GdhRjQ GdaGUds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3eJaQbGJs